Perancangan model pembelajaran Project Base Learning (Outdoor) Karst Maros Prodi Pendidikan Geografi FMIPA UNM - Suprapta Suprapta; Ibrahim Abbas; Maddatuang Maddatuang (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The design of learning models that are trained withthis mentoring model emphasizes more on reconstructing themindset. Therefore, in the construction of the knowledgeembedded that the Project Based Learning model (out-door)contains the principle of the ability to plan projects and workwith the working principles of scientists. It is realized that thegoal is hard to be attained. Besides, based on the character ofthe SM3T PPG participants, it is known that there aredifferences of the tertiary institutions origin and differentacademic climates among those institutions. Moreover, thereare differences in practical experience in the field. Trainingand constructing knowledge through many practices will fostera level of employability. The 2013 curriculum that has notbeen truly understood of every prospective teacher and eventhe teacher demands to continue to be trained. For this reason,an intensive mentoring model was chosen because it wasconsidered more effective. To achieve these objectives, theseactivities were chosen: 1) FGD to determine learningobjectives and location of objects; 2) FGD of the possibility tofind concepts in the field; 3) Field and object orientation; 4)Discussion in the field on object findings; 5) Discussion in thefield on details of object findings; 6) FGD of findings on thephenomenon of concepts and field findings. The results in theLearning Implementation Planning of the Project BasedLearning model (out-door) included: 1) Determination ofinitial location based on indicators and learning objectives; 2)Estimation of concepts that can be obtained at the learninglocation; 3) Classification and understanding of the ginesaprocess of landform and its object; 4) Deepening of the objectof ginesa as detailed as possible.